2 books co-published by UMP and Abad Sinergi receive ABN 2022 - Shalfarina, Shahriman (2022)
AYER KEROH, 22 February 2022 – Two books jointly published between Universiti Malaysia Pahang (UMP) Press and Abad Sinergi Sdn. Bhd. has received two prestigious awards in the National Book Award Ceremony 2022 (ABN 2022) through the writings of Datuk Associate Professor Dr. Wan Ahmad Fauzi bin Hashim@Wan Husain from the Faculty of Industrial Management (FPI).